LEGAL CONSEQUENCES OF THE MAINTENANCE PROVIDER’S DEATH ARISING FROM A LIFETIME MAINTENANCE AGREEMENT - Krstić, Novak (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
The Inheritance Law of the Republic of Serbia regulates only certain legal consequences of the prior death of the provider of support, leaving numerous contentious issues unresolved. The legislator has chosen to authorize only the spouse and descendants of the deceased provider of support, who are entitled to inherit from him, to continue providing support if they agree to do so. The legal consequences of contract termination are specifically regulated in cases where these heirs are unable or unwilling to continue the agreement. The paper critically examines the existing solutions regarding the circle of subjects entitled to continue providing care and support, discusses the procedure by which they declare whether they are able and willing to continue the agreement, and points out that the recipient does not have the right to declare whether they agree to the continuation of the contract, which may place them in a disadvantaged position. The author argues that the circle of heirs who can continue the agreement should be expanded to include all heirs who lived with the recipient and participated in their support during the provider’s lifetime. Given that the law does not grant the recipient the right to decide whether they wish to be supported by the heirs of the provider, the paper suggests that, in order to protect the recipient’s interests, they should be granted the right to request the termination of the agreement within a reasonable period (six months or one year) without the need to specify a particular reason. Furthermore, the paper highlights the legislator’s failure to regulate numerous unresolved issues and presents views on the legal consequences that would arise in various real-life situations, which should be regulated de lege ferenda.